1988
DOI: 10.1051/jphyscol:1988651
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Granular Bainite

Abstract: A 2.25Cr - 1Mo - 0.1C welded steel having a microstructure described as "granular bainite" has been investigated using optical microscopy, electron microscopy and atom probe field ion microscopy. Granular bainite was found to consist of bainitic ferrite and retained austenite, but no cementite. Grains of ferrite are built up by parallel platelike subgrains - bainitic ferrite. The carbon concentration changes abruptly at the ferrite - retained austenite interface but no diffusion of substitutionals could be det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Based on its morphology, the bainite formed in this temperature range is sometimes called granular bainite. [29,30] In the comprehensive article by Steven and Haynes [27] in which they investigated many British Standards (B.S.) En steels, this incomplete transformation effect was already noted and was quantified to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…Based on its morphology, the bainite formed in this temperature range is sometimes called granular bainite. [29,30] In the comprehensive article by Steven and Haynes [27] in which they investigated many British Standards (B.S.) En steels, this incomplete transformation effect was already noted and was quantified to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…During this gap, it can be inferred that the shear train caused by bainite transformation was partially released. Regarding GB, an unusual type of bainite due to the absence of cementite [16], boundary dislocations are not accumulated because of its ferritic matrix with diffusional transformation mode [29]. Finally, some results reported in previous studies were confirmed, e.g., lower dislocation density in bainite that transformed earlier than martensite [30].…”
Section: Determination Of Strain Distribution and Dislocation Densitymentioning
confidence: 53%
“…In Figure 2c, GB was obtained when the specimen was cooled at 0.05 • C/s. GB is indeed characterized by the absence of carbides and by the presence of isolated martensite-austenite (M-A) constituents [16]. M-A islands appear in grey and are distributed in the ferritic matrix that is dark in the SEM image shown.…”
Section: Morphologic Featuresmentioning
confidence: 99%
“…Granular bainite is an equiaxed bainitic ferrite structure with discrete islands of MA constituent. Granular bainite is formed due to slow cooling and high silicon content [17]. High Si prevents the cementite forming, resulting in formation of blocky ferrite with MA phase.…”
Section: Microstructural Analysismentioning
confidence: 99%